A profile of the global airline industry - Gourdin, Kent N., (Industry profiles collection., 2016)
The airline industry is one of the most fascinating in the world, with roots going back to the earliest years of the 20th century. Not long after the Wright brothers flew successfully for the first time in 1903, interest in aviation for military and commercial purposes began. In the late teens, the U.S. government began offering potentially lucrative airmail contracts to start-up air carriers, who competed vigorously for them often with disastrous results. Despite the rocky start, the carriers persevered and, by the 1930s, were beginning to look like the companies we see today. This book will provide the reader insight into the nature of the airlines and why companies promulgate the strategies they do. First, the history of commercial air services will be examined, with an initial focus on the United States. After this background, airline operations around the world will be compared and the different types of carriers that comprise the industry will be discussed. Next, the reader will learn about important uncontrollable outside forces (fuel costs, terrorism, economic conditions, etc.) that can have dramatic and potentially devastating impacts on an airline. A discussion of economic regulation and deregulation will follow to help the reader understand the impact of both legislate actions on the carriers operating today. Finally, in the face of expected increases in the demand for the global movement of passengers and cargo, future opportunities and challenges facing the airline industry will be presented.